National report compliance monitoring of lead paint standard in Nepal. - Sah, Ram Charitra (CEPHED., 2021)
SUMMARY: Lead is a toxic metal that causes adverse effects on both human health and the environment. While lead exposure is also harmful to adults, lead exposure harms children at much lower levels, and the health effects are generally irreversible and can have a lifelong impact. The younger the child, the more harmful lead can be, and children with nutritional deficiencies absorb ingested lead at an increased rate. The human fetus is the most vulnerable, and a pregnant woman can transfer lead that has accumulated in her body to her developing child. Lead is also transferred through breast milk when the lead is present in a nursing mother. Evidence of reduced intelligence caused by childhood exposure to lead has led the World Health Organization (WHO) to list "lead-caused mental retardation" as a recognized disease. WHO also lists it as one of the top ten diseases whose health burden among children is due to modifiable environmental factors. Lead paint is a major source of childhood lead exposure. The term lead paint is used in this report to describe any paint to which one or more lead compounds have been added. The cut-off concentration for lead paint used in the report is 90 parts per million (ppm, dry weight of paint), the strictest legal limit enacted in the world today and also by the Government of Nepal. All lead concentrations in the report are total lead levels unless otherwise specified. The lead paint standard promulgated by the Government of Nepal, Ministry of Forest and Environment-MOFE (the then MOEST)) through a gazette notification dated 22 December 2014 with its effective dates 181 days after this notification i.e., from 20th June 2015. It has three important provisions: (a). Maximum lead-in paints imported and domestically produced in Nepal to be not more than 90 ppm; (b) Each paint cans should be labeled with lead content in the paint it contained, and (c) Each paint cans should also be labeled with a protective precautionary message for occupational safety.. Most highly industrial countries adopted laws or regulations to control the lead content of decorative paints-the paints used on the interiors and exteriors of homes, schools, and other child-occupied facilities-beginning in the 1970s and 1980s. In Nepal, the lead paint standard was enacted through a gazette notification on 22 December 2014 with the effective date after 181 days i.e., 20th June 2015 required to be effectively implemented for limiting the amount of lead in paint for all uses as well as should fully adhere the mandatory labeling provision. From July to August 2021, the CEPHED collected a total of 62 cans of solvent-based paint imported, produced, and sold from stores in some 20 cities viz Dhankuta, Biratnagar, Bhardah, Janakpur, Birgunj, Simara, Hetauda, Bharatpur, Pokhara, Damauli, Dhangadhi, Birendranagar, Nepalgunj, Butwal, Bardaghat, Kathmandu, Lalitpur, Thimi, Mahalaxmi and Bhaktapur of all seven provinces of Nepal. The majority of purchased paints (48 samples) were from 30 National Paints Companies, 9 paints samples from three multinational Paints companies (Asian, Berger Jenson & Nicolson, and Kansai Nepal Paints), and 5 paints samples from 4 International paint manufacturing companies from India, Thailand, and the USA. The paints represented 41different brands produced by 37 (30 National, 3 Multinational, 4 International) manufacturers. Altogether 17 different sheds of 9 broad color paints were included in the samples. Most of these samples were recently produced in the years 2020 and 2021 and no samples were included in the study of older that the Government of Nepal (GON) Lead Paints Standard took effect. All paints were analyzed by an accredited laboratory Nepal Environmental and Scientific Services (NESS) Limited in Nepal for their lead content, based on the dry weight of the paint. The test method applied for lead concentration analysis was direct air acetylene AAS, AOAC, 974.02. The accredited laboratory participates in the Association of Officials Analytical Chemists, assuring the reliability of the analytical results. The analytical methods adopted by the AOAC (Association of Official Analytical Chemists) are used by government agencies concerned with the analysis of fertilizers, foods, feeds, pesticides, drugs, cosmetics, hazardous substances, and other materials related to agriculture, health and welfare, and the environment. AOAC methods are also used by industries to check the compliance of their products.